The Responsibility of the Causer According to the Principles of the Iraqi Penal Code - Fadhil Rekib, Assist. Prof .Emad; Tariq Ebrahim, Prof. Dr. Nawal (Basra studies journal, 2024)
The difference in jurisprudence trends about the causer responsibility for the criminal result, between those who support his responsibility and those who reject it, it may result in a difference in its judgment in the penal laws according to the criterion adopted by the legislator when formulating its general rules. In view of the lack of clarity in ruling the criminal causer in terms of their responsibility for the criminal outcome in light of Article 29 of the Iraqi Penal Code No. 111 of 1969 (amended) contained in the general principles, it may varied the position of jurisprudence and the judiciary in its interpretation, Which prompted us to research this topic in order to determine the jurisprudence trend adopted by the Iraqi legislature on causation and then determine the responsibility of the causer in the light of the Iraqi Penal Code.